Morigeración del régimen de nulidades del proceso civil vía acción de tutela (2021)
The ineffectiveness of procedural acts, particularly in relation to invalidity, has been relativized through the action of protection against judicial decisions. In effect, the textual nullities in the civil procedure law have declined, in different case law decisions, in a flexible system of nullities. The ordinary judge is tied to a closed list of cause of nullity, but the judge who decides the action of protection against judicial decisions can declared the ineffectiveness of a procedural act for formal irregularities that are not necessarily regulated by the lawmaker. This particular case suggests an unequal treatment in respect of the same facts, the violation of the foreseeability of procedural forms, the need to recognize the consequences of the action of protection in the civil process and the opening of the nullity system in favor of a more flexible system of nullities through the incorporation of a virtual nullity for a breach of the right to due process.